Development of an attenuation mechanism targeting the structure-function of the West Nile virus envelope protein - Maloney, Bailey Elizabeth (Kansas State University, 2023)
Flaviviruses cause human diseases. Live-attenuated vaccines (LAVs) that elicit long-lasting immunity with one immunization are only available for yellow fever virus (YFV) and Japanese encephalitis virus. Developing candidate LAVs for flaviviruses is a public health priority, and the rational design of candidate LAVs can ensure safety. This dissertation examined the flavivirus conserved structure-function of the envelope (E) protein. We used West Nile virus (WNV) and YFV as models to generate the knowledge of how the E protein drives membrane fusion. The conformational change of the E protein from dimer to trimer induces the membrane fusion process. Formation of the E protein trimer requires rearranging three domains (EDI, EDII, and EDIII). Dissociation of the E protein dimer is due to the movement of EDII against EDI, forming an intermediate structure that is stabilized by the movement of EDIII against EDI. Therefore, the dimer-to-trimer transition involves two interdomain movements called the EDI-EDII hinge region and EDI-EDIII linker. We hypothesize that mutations of the flavivirus conserved amino acids in the EDI-EDII hinge region or EDI-EDIII linker can attenuate the virulence phenotype of multiple flaviviruses in mice. Mutations of flavivirus-conserved residues in each interdomain region were characterized using the infectious clones of the WNV NY99 strain and YFV Asibi strain. The E-A54I and E-Y201P mutations in the EDI-EDII hinge region and the E-L295S mutation in the EDI-EDIII linker can fully attenuate the mouse neuroinvasive phenotype of WNV NY99. The E-V188T mutation in the EDI-EDII hinge region can fully attenuate the virulence phenotype of YFV Asibi. Our findings demonstrated that the EDI-EDII hinge region and the EDI-EDIII linker are crucial for the structure-function of the E protein, and identified residues are worthwhile investigating for a flavivirus-common attenuation strategy.
Keywords: Flavivirus; Attenuation mechanism; Envelope protein; West Nile virus